Comparative morphology of the first zoea of twelve brachyuran species (Crustacea: Decapoda) from the Amazon region - Souza,Adelson S. de (2013)
The laboratory-hatched first zoeal stage of twelve brachyuran species collected in the estuarine area of the Caeté River in the Amazonian region are described and illustrated in the present study: P. americanus Saussure, 1857, Eurytium limosum (Say, 1818), Sesarma curacaoense De Man, 1892, S. rectum Randall, 1840, Armases rubripes (Rathbun, 1897), Aratus pisonii (H. Milne Edwards, 1837), Ocypode quadrata (Fabricius, 1787), Uca rapax (Smith, 1870), U. maracoani (Latreille, 1802), U. thayeri Rathbun, 1900, Ucides cordatus (Linnaeus, 1763) and Pachygrapsus gracilis (Saussure, 1858). Through intraspecific comparisons of the respective larval stage, an identification key was generated and provided. Most of the studied species presented morphological differences (e.g. type and presence or absence of setae) when compared to the same species previously described in the literature.